Synthesis, optoelectronic, and transistor properties of BODIPY- and cyclopenta[c]thiophene-containing pi-conjugated copolymers - Debnath, Sashi; Singh, Saumya; Bedi, Anjan; Krishnamoorthy, Kothandam; Zade, Sanjio S. (Journal of Physical Chemistry C, 2015)
Three new low-band-gap copolymers were synthesized by fusing dipyrromethene difluoroborane (BODIPY) as the acceptor (A) and thiophene-capped 5,5-bis(hexyloxymethyl)-5,6-dihydro-4H-cyclopenta[c]-thiophene (CPT) as the donor (D). The BODIPY unit was copolymerized through the `alpha' positions (1 and 7 positions) in P1 and through the `beta' positions (2 and 6 positions) in P2 and P3. The additional acetylene unit between D and A in P3 enhanced the conjugation by minimizing the possible steric hindrance compared to that in P2, whereas P1 exhibited a more red-shifted absorption than P2 and P3 because of the more effective conjugaion through the `alpha' positions of BODIPY. Importantly, the optical band gaps (E-g(opt)) obtained from the onset of the absorption spectra are 1.28, 1.71, and 1.57 eV for P1, P2, and P3, respectively. P1 has the lowest band gap for any CPT-containing polymer. In the best transistor devices, a mobility improvement by 4 orders of magnitude from 3.22 x 10(-6) cm(2) V-1 s(-1) for P2 to 0.01 cm(2) V-1 s(-1) for P1 was achieved. DFT calculations alongside measured charge-transport properties indicated that appreciable alterations in the optoelectronic properties of the polymers were achieved through minor changes in their structural features. The polymers were further characterized by thin-film X-ray diffraction, atomic force microscopy, and spectroelectrochemistry to investigate their material and electrochemical properties.